Seasonality in late-Holocene climate from ice-core records - Morgan, VI; Tasman van Ommen (1997)
High-resolution ice-core Î´ 18 O data from a site with well preserved seasonal cycles aye used to extract seasonal temperature trends over the last 700 years with an effective resolution of a few months. Examination of this record on timescales of decades to centuries shows distinctly different patterns of temperature variation between summer and winter. Over the last 700 years, the summer months show relatively little change, with the Coolest summers occurring early this century. The winters, in contrast, show significant fluctuations including a period of warmer temperatures between AD 1400 and 1500 and a colder period centred around the early 1800s which corresponds to the latter part of an era of glacier advance and cold winters in Europe sometimes known as the 'Little Ice Age' (LIA). Since many proxy temperature indicators respond principally to seasonal extremes, they will consequently give biased results in the presence of seasonally confined trends. This may account for the fact that events such as the LIA do not appear in some records.